Technocracy as a concept of social theory and a type of thinking - Шоріна, Т. Г. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2017)
The paper examines a technocratic understanding of the social evolution and discloses the essence of technocratic rationality as a way of metaphysical thinking. А technocratic position is considered as a conceptual principle of understanding of a society dynamics in which its technical side to be absolutized and at the same time its social and humanitarian sides are detracted. It is proved that technocratic concepts are a form of metaphysical reflection of the capitalist economy realities and right-liberal ideology.